Borrelia burgdorferi Infection in Biglycan Knockout Mice - Cuellar J.; Pietikäinen A.; Glader O.; Liljenbäck H.; Söderström M.; Hurme S.; Salo J.; Hytönen J. (Oxford University Press, 2025)
Background: Borrelia burgdorferi sensu lato spirochetes (Borrelia) causing Lyme borreliosis are able to disseminate from the initial entry site to distant organs in the host. Outer-surface adhesins are crucial in the bacterial dissemination and adhesion to various tissues. Two well-characterized Borrelia adhesins, decorin-binding proteins A and B, have been shown to bind to 2 host receptors, decorin and biglycan. However, the role of biglycan in Borrelia infection has not been characterized in vivo.
Methods: We infected biglycan knockout (KO) and wild-type (WT) C3H mice with strains representing 3 Borrelia genospecies, Borrelia burgdorferi sensu stricto, Borrelia garinii, and Borrelia afzelii. The infection was monitored by measuring joint swelling, Borrelia culture, polymerase chain reaction analysis, and serologic analysis. The host immune responses were analyzed by histological scoring of the inflammation in tissues and by cytokine profiling.
Results: B. burgdorferi sensu stricto and B. garinii established long-term infection in mice of both genotypes, while B. afzelii failed to disseminate in KO mice. Further, the B. burgdorferi sensu stricto–infected KO mice had persistent inflammation in the joints.
Conclusions: The dissemination and tissue colonization of Borrelia and the inflammatory response of the host differ in a mouse biglycan expression– and Borrelia genospecies–dependent manner.